2017
DOI: 10.1002/dys.1555
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well‐being Trajectories of Individuals with Dyslexia Aged 3–11 Years

Abstract: Dyslexia has been associated with a range of psychological well-being issues in childhood. However, it is unclear if these difficulties stem from coping with academic struggles at school, or from other pre-existing diagnoses that sometimes co-occur with dyslexia. Using UK Millennium Cohort Study data (n = 7224) from 2003 to 2011, the present study compared psychological well-being development from ages 3-11 years for children with (1) dyslexia only; (2) special educational needs excluding dyslexia; (3) comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…that lead to negative feelings about their own performance and well-being. These results are in line with previous research that has pointed in the same direction [26][27][28].…”
Section: Emotional State and Dyslexiasupporting
confidence: 94%
“…that lead to negative feelings about their own performance and well-being. These results are in line with previous research that has pointed in the same direction [26][27][28].…”
Section: Emotional State and Dyslexiasupporting
confidence: 94%
“…In line with this finding, Panicker and Chelliah (2016), in a study in which adolescents with LD were contrasted with a peer group with borderline intellectual functioning, reported that the adolescents with LD had a low level of resilience, indicating inadequate coping skills, and that their depression and anxiety levels increased with age. These results were supported by a later finding that upon reaching school age, individuals with RD showed a decline in wellbeing compared to children without RD (Jordan & Dyer, 2017). It is reasonable to assume that individuals with RD are more dissatisfied with their lives than non‐RD peers (Miller, 2002).…”
Section: Introductionsupporting
confidence: 61%
“…A critical problem in reading intervention research is what interventions are effective with children who struggle with reading acquisition despite receiving high‐quality Tier 1 and 2 instruction. These children, called persistently poor readers , have an increased risk for major academic difficulties and a cascading risk of socio‐emotional, attentional and behavioural problems if their intervention needs are not met (e.g., Jordan & Dyer, 2017; Parhiala et al, 2015). In this study, we aimed to examine the effects of two Tier 3 intervention programmes on the reading and spelling skills of persistently poor readers in Grade 3.…”
Section: The Present Studymentioning
confidence: 99%